How academic podcasting can change academia and its relationship with society: A conversation and guide - Cox, Michael; Harrison, Hannah L.; Partelow, Stefan; Curtis, Steven; Elser, Stephen R.; Hammond Wagner, Courtney; Hobbins, Robert; Barnes, Conor; Campbell, Lisa; Cappelatti, Laura; De Sousa, Emily; Fowler, Julie; et al. (Frontiers in Communication, 2023)
In this paper we explore the potential of academic podcasting to effect positive change within academia and between academia and society. Building on the concept of "epistemic living spaces", we consider how podcasting can change how we evaluate what is legitimate knowledge and methods for knowledge production, who has access to what privileges and power, the nature of our connections within academia and with other partners, and how we experience the constraints and opportunities of space and time. We conclude by offering a guide for others who are looking to develop their own academic podcasting projects, and discuss the potential for podcasting to be formalized as a mainstream academic output.